PENERAPAN METODE PEMBELAJARAN COOPERATIVE SCRIPT DALAM PROSES PEMBELAJARAN PENDIDIKAN PANCASILA KURIKULUM MERDEKA DI SEKOLAH MENENGAH KEJURUAN NEGERI 1 KENDAL - Nofia, Chotimatul; Widodo, Suwarno; Suneki, Sri (FPIPSKR Universitas PGRI Semarang, 2024)
This research is motivated by student collaboration in group work, student activity is still not optimal and some teachers are still not using varied and innovative learning methods. This research aims to describe the application of the Cooperative Script Learning Method in the Independent Curriculum Pancasila Education Learning Process at SMK N 1 Kendal. This study used descriptive qualitative method. Data collection techniques include observation, interviews and documentation. Data analysis techniques through data collection, data reduction, data presentation and data withdrawal. This research shows the results of 1) Planning, educators create, prepare teaching modules referring to the independent curriculum and the flow of learning objectives. 2) Implementation, the teacher opens the class, the teacher divides the students into pairs of classmates, the teacher shares the material and asks the students to summarize, the teacher instructs the students to first determine the role of speaker and listener, the teacher instructs the speaker students to read the summary and includes the main idea, the teacher instructs the listener students to research / correcting/showing incomplete main ideas, the teacher instructs students to change roles, the speaker becomes a listener, the teacher provides conclusions with the students, the teacher checks students' understanding by answering questions and the teacher closes the lesson. 3) Evaluation, the teacher carries out written and oral evaluations. the research was carried out well. However, students are less active in asking questions and lack time. students are more active in asking questions and teachers manage their time appropriately.